Nanoscale LaDySn2O7/SnSe Composite for Visible‐light Driven Photoreduction of CO2 to Methane and for Monoazo Dyes Photodegradation. Issue 39 (21st October 2019) - Karamat, Nazia; Ashiq, Muhammad Naeem; Joya, Khurram Saleem; Ijaz, Sana; Sharif, Muhammad; Ehsan, Muhammad Fahad; Sher, Muhammad; Ul‐Haq, Najam
Abstract: Photoactive materials provide a greener way to convert solar radiation into chemical energy, fuels and for the photodegradation of organic pollutants. We show here nanostructured LaDySn2 O7 /SnSe composite that effectively harvests in the visible‐spectrum and performs actively for CO2 reduction and photodegradation of foron blue (FB) dye. Various spectroscopic methods and characterization techniques are employed to explore the structural, morphological, compositional, surface area, optical properties, oxidation states of the elements and valence band position. The optical properties of SnSe revealed their action as photosensitizers for stannate pyrochlore LaDySn2 O7 under visible–light irradiation. Admirable photoreduction efficiency for CO2 conversion into methane was achieved for composites relative to individual catalysts. They also show superior photocatalytic degradation > 98.8% for foron blue dye. Whereas, individual photocatalyst LaDySn2 O7 is photo‐insensitive in the visible region due to large band gap and the cocatalyst (SnSe) exhibited photodegradation up to 15.5%. No observable deactivation of LaDySn2 O7 /SnSe was recorded after the five consecutive recycles runs for photodegradation of foron blue dye. Abstract : Nanoscale LaDySn2 O7 /SnSe composites are synthesized successfully as visible light‐responsive materials. The composite system performs well regarding the photocatalytic activity for CO2 reduction to methane with good efficiency, and for monoazo dye photodegradation under mild chemical conditions.